2011
DOI: 10.1097/brs.0b013e31821bcf4c
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Function in Adolescent Idiopathic Scoliosis Relative to the Surgical Procedure

Abstract: Intraoperative chest wall violation produced detrimental pulmonary effects, as reflected by reduced percent-predicted values at 10-year follow-up. Posterior-only procedures, which spared the chest wall, showed significant improvements in FVC and FEV(1) absolute values without any change in percent-predicted values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
54
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(56 citation statements)
references
References 39 publications
0
54
0
2
Order By: Relevance
“…However, APVCR had fallen out of favor for several factors. Anterior transthoracic procedures were challenging for most orthopedists and proved to have detrimental effects on pulmonary function [33][34][35][36][37]. And it was difficult to approach the concavity of the angular kyphosis in deformities greater than 60° [25].…”
Section: Discussionmentioning
confidence: 98%
“…However, APVCR had fallen out of favor for several factors. Anterior transthoracic procedures were challenging for most orthopedists and proved to have detrimental effects on pulmonary function [33][34][35][36][37]. And it was difficult to approach the concavity of the angular kyphosis in deformities greater than 60° [25].…”
Section: Discussionmentioning
confidence: 98%
“…(34) Pulmonary reserves peak in the second decade of life and gradually decline as the patient ages. (16,35,36) Impairment in pulmonary function, which is expected with progression of scoliotic curvature, may be controlled with surgical correction. Therefore, pulmonary impairment from spinal deformity remains an indication for surgical intervention for AIS.…”
Section: Discussionmentioning
confidence: 99%
“…(7) Previous studies have indicated that severe scoliosis leads to poor pulmonary function. (2)(3)(4)(5)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17) Since poor pulmonary function may lead to a higher incidence of postoperative pulmonary complications, preoperative pulmonary function tests (PFTs) have commonly been used to predict postoperative pulmonary complications. (14) However, there have been no detailed analyses of preoperative pulmonary function in relation to the Cobb angle, location of apical vertebrae and age in AIS.…”
Section: Introductionmentioning
confidence: 99%
“…Scoliosis is a three-dimensional distortion of the spine and chest cage, which typically produces a reduction in pulmonary function. This reduction may be a result of chestcage stiffness, reduced hemidiaphragmatic movement, and uneven distribution of inhaled air in the lung (decreased on the convex side of the curve) 12,20 . Therefore, some surgeons have postulated that surgical correction for adolescent idiopathic scoliosis can improve not only the structural deformity, but may affect long-term pulmonary function 21 .…”
mentioning
confidence: 99%
“…We also found that revision surgery more frequently resulted in a clinically significant decline in pulmonary function (36% of patients compared with 22% of patients who underwent primary surgery); however, surgical approach and UIV did not significantly affect pulmonary function test results. Numerous studies have investigated the topic of longterm pulmonary function in young patients (less than eighteen years of age) who undergo surgery for adolescent idiopathic scoliosis [9][10][11][12][13][14][15][16][17][18][19] . Scoliosis is a three-dimensional distortion of the spine and chest cage, which typically produces a reduction in pulmonary function.…”
mentioning
confidence: 99%